Influence of Psychological Factors, Social Factors and Physical Factors on Student Satisfaction that Impacts on Lecturer Performance in Private Universities in Palembang City - Agusria, Lesi; Fitriah, Wani (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
This research discusses the formulation of whether the influence of psychological factors, physical factors and social factors on Student Satisfaction impacted the performance of lecturers at Private Universities in Palembang City. This type of research is associative using samples of 245 students with sampling techniques using probability sampling. The data used in this study is primary data collected through the Kuesioner method. Data analysis techniques are performed with multiple linear regression two models using SPSS ver.26. The results showed that (1). Psychological factors have a significant effect on student satisfaction at Palembang City Private College, and there is an indirect influence of psychological factors (X1) through Student Satisfaction (Y) on lecturer performance (2). Social factors have a significant effect on student satisfaction at private universities in Palembang, and there is an indirect influence of social factors (X2) through Student Satisfaction (Y) on lecturer performance (3). Physical factors have a significant effect on student satisfaction in private universities in Palembang city, and there is an indirect influence of physical factors (X2) through Student Satisfaction (Y) on lecturer performance (Z).